Association between depression and quality of life among Brazilian older adults in long-term care facilities - Souza, Marina Celly Martins Ribeiro; Acuna, Nicholas; Horta, Natália de Cássia; Borges, Carolina Marques; Lacerda, Tatiana Teixeira Barral (Revista Kairós-Gerontologia, 2019)
This study aims to test the association between geriatric depression and the quality of life of older adults in long-term care facilities in Brazil. Results showed that there was a significant correlation among four of the six domains that were measured in the WHOQOL-OLD questionnaire of those demonstrating symptoms and those without. In conclusion, higher depression scores were reported by participants who had lower quality of life scores. Mental health care should be carefully addressed among institutionalized older adults in long-term facilities. Keywords: Geriatric; Long-term care facilities; Quality of life; Depression, Brazil.